Decreased Volume of Lateral and Medial Geniculate Nuclei in Patients with LHON Disease—7 Tesla MRI Study - Jonak, Kamil (J Clin Med, 2020)
Leber’s hereditary optic neuropathy (LHON) is a maternally inherited genetic disorder leading to severe and bilateral loss of central vision, with a young male predilection. In recent years, multiple studies examined structural abnormalities in visual white matter tracts such as the optic tract and optic radiation. However, it is still unclear if the disease alters only some parts of the white matter architecture or whether the changes also affect grey matter parts of the visual pathway. This study aimed at improving our understanding of morphometric changes in the lateral (LGN) and medial (MGN) geniculate nuclei and their associations with the clinical picture in LHON by the application of a submillimeter surface-based analysis approach to the ultra-high-field 7T magnetic resonance imaging data. To meet these goals, fifteen LHON patients and fifteen age-matched healthy subjects were examined. A quantitative analysis of the LGN and MGN volume was performed for all individuals. Additionally, morphometric results of LGN and MGN were correlated with variables covering selected aspects of the clinical picture of LHON. In comparison with healthy controls (HC), LHON participants showed a significantly decreased volume of the right LGN and the right MGN. Nevertheless, the volume of the right LGN was strongly correlated with the averaged thickness value of the right retinal nerve fiber layer (RNFL). The abnormalities in the volume of the LHON patients’ thalamic nuclei indicate that the disease can cause changes not only in the white matter areas constituting visual tracts but also in the grey matter structures. Furthermore, the correlation between the changes in the LGN volume and the RNFL, as well as the right optic nerve surface area located proximally to the eyeball, suggest some associations between the atrophy of these structures. However, to fully confirm this observation, longitudinal studies should be conducted.